Understanding Mechanical Ventilation A Practical Handbook - Hasan, Ashfaq; SpringerLink (Online service) (London : Springer London, 2010)
The care of patients with multiple life-threatening problems is a monumental challenge. Burgeoning information has deluged the generalist and placed increasing reliance on the specialist. Predictably, this has led to the evolution of a team approach, but this does not assist the novice in critical care, with little practical and relevant information available on learning specific procedures and best practice. This new edition of Understanding Mechanical Ventilation: a Practical Handbook familiarizes physicians, nurses and respiratory technologists with the concepts that underlie mechanical ventilation. Physiological concepts are stressed throughout this book in order to address the specifics of mechanical ventilation, while currently accepted strategies for patients with specific disorders are reviewed in detail. Ventilator waveforms, airway humidification, aerosol therapy and the use of novel software-based modes of ventilation in the ICU are also included. The emphasis throughout the book is on presenting material in a reader-friendly, practical style incorporating numerous figures and tables. In this way, it will be a vital reference to all involved in the management of patients requiring mechanical ventilation in the ICU.
Historical Aspects of Mechanical Ventilation -- The Indications for Mechanical Ventilation -- Physiological Considerations in the Mechanically Ventilated Patient -- The Conventional Modes of Mechanical Ventilation -- Ventilator Settings -- Ventilator Alarms -- Monitoring Gas Exchange in the Mechanically Ventilated Patient -- Monitoring Lung Mechanics in the Mechanically Ventilated Patient -- Mechanical Ventilation in Specific Disorders -- The Complications of Mechanical Ventilation -- Ventilator-Associated Pneumonia -- Discontinuation of Mechanical Ventilation -- Noninvasive Ventilation in Acute Respiratory Failure -- Negative Pressure Ventilation -- Airway Humidification in the Mechanically Ventilated Patient -- Aerosol Therapy in the Mechanically Ventilated Patient -- Nonconventional Modes and Adjunctive Therapies for Mechanical Ventilation -- Case Studies.
Keywords: Medicine; Anesthesiology; Critical care medicine; Pneumology; Medicine & Public Health; Intensive / Critical Care Medicine; Anesthesiology; Pneumology/Respiratory System